2019
DOI: 10.1002/pros.23869
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of a 68Ga‐PSMA PET/CT prospective study in prostate cancer patients with occult recurrence: Diagnostic performance and impact on therapeutic decision‐making

Abstract: Background In this prospective study (NCT03443609), we investigated the impact of 68Ga‐PSMA‐11 PET‐CT on the treatment plan and therapeutic response obtained for patients with prostate cancer (PCa) presenting a recurrence with a low rising PSA. Methods One hundred thirty hormone‐naive (PSA < 1.5 ng/mL) patients were enrolled. All patients received radical treatment. PET images were recorded 1 and 2  hours after injection of tracer and interpreted by two independent nuclear physicians. Six months after treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 22 publications
(59 reference statements)
0
18
1
Order By: Relevance
“…Ultimately 16 studies were included in the review (Tab. 2; [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]). Twelve studies reported outcomes using [ 68 Ga]-PSMA-11 PET, while four studies reported data on other PSMA-tracers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately 16 studies were included in the review (Tab. 2; [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]). Twelve studies reported outcomes using [ 68 Ga]-PSMA-11 PET, while four studies reported data on other PSMA-tracers.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled data of all patients included in this review show an overall change of management in 861 of 1899 patients (45%). Nine studies, including 729 patients, reported sufficient data to extract the kind of change in management [20,24,26,27,29,33,36,38,40]. In 332 (46%) of these 729 patients a change in management was seen.…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies in which all patients underwent extended pelvic lymph node dissection appeared to confirm the accuracy of the Roach equation (9). PSMA PET and fluciclovine 18 F PET studies have demonstrated the role of molecular imaging in physician decision making among patients with biochemical recurrence as well as in the upfront setting among patients with intermediate-and high-risk prostate cancer at the time of initial diagnosis (10)(11)(12)(13)(14).…”
mentioning
confidence: 90%
“…PSMA PET has demonstrated strong impact on therapy planning and clinical decision making with treatment regimen adjustment in 27%-77% of patients [136][137][138][139][140][141][142][143][144] [120]. Since then numerous original research and review articles have pointed out that the PSMA imaging using PET/CT is a sensitive, specific, safe, efficient and reproducible diagnostic method allowing visualization of local disease, lymph node, bone, and visceral organ lesions with high detection rate, and it has positive predictive value [121][122][123][124][125][126][127][128].…”
Section: Impact Of Psma-targeted Radiopharmaceuticals On Patient Treamentioning
confidence: 99%
“…PSMA PET has demonstrated strong impact on therapy planning and clinical decision making with treatment regimen adjustment in 27%-77% of patients [136][137][138][139][140][141][142][143][144] Tc-PSMA scintigraphy has minimally less noise than posttherapy scanning and can be used for imaging follow-up in out-patient setting. GM 5 geometric mean; MIP 5 maximum-intensity projections; p.i.…”
Section: Impact Of Psma-targeted Radiopharmaceuticals On Patient Treamentioning
confidence: 99%